MENIMBANG ULANG KONSEP PERAN LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MENDORONG INKLUSI KEUANGAN DIGITAL - usman, usman; Suhartina (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
Digital transformation in the financial sector has become an urgent necessity to achieve financial inclusion, particularly for underserved communities. Islamic Microfinance Institutions (LKMS), such as Baitul Maal wat Tamwil (BMT) and Islamic cooperatives, play a strategic role in empowering grassroots economies, especially in rural areas. However, the digitalization of LKMS faces various challenges, including limited digital infrastructure, low digital literacy among managers and clients, and regulatory constraints. This study aims to analyze the role of LKMS in promoting digital financial inclusion, identify the barriers they face, formulate practical strategies, and explore potential collaborations with Islamic fintech. By applying a contextual analysis approach and integrating Islamic financial principles, this research is expected to contribute both theoretically and practically to the development of effective and sustainable LKMS digitalization